1993
DOI: 10.1016/0378-1097(93)90582-m
|View full text |Cite
|
Sign up to set email alerts
|

Porins and lipopolysaccharide of Escherichia coli ATCC 25922 and isogenic rough mutants

Abstract: The lipopolysaccharide and porin profile of Escherichia coli ATCC 25922, a smooth strain commonly used in antibiotic susceptibility testing, and five isogenic rough mutants was examined. The lipopolysaccharide of the parent strain had the characteristic ladder pattern on polyacrylamide gels, while that of the mutants appeared similar to chemotypes Ra and Rc of Salmonella typhimurium with some changes in chemical composition. Of the porins, OmpC appeared markedly reduced in the parent strain while OmpF appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…After 24 hours, LPS was purified and subjected to SDS-PAGE as described [51] (Figure 7). Of the LPS bands characteristic of the ATCC® 25922™ isolate [52], ciclopirox reduced the concentrations of the highest molecular weight band (∼20 kDa) as well as the O-antigen bands (37–50 kDa), as indicated by the arrows (Figure 6). LPS isolated from MG1655, which lacks an O-antigen, was unchanged in the presence of ciclopirox.…”
Section: Resultsmentioning
confidence: 94%
“…After 24 hours, LPS was purified and subjected to SDS-PAGE as described [51] (Figure 7). Of the LPS bands characteristic of the ATCC® 25922™ isolate [52], ciclopirox reduced the concentrations of the highest molecular weight band (∼20 kDa) as well as the O-antigen bands (37–50 kDa), as indicated by the arrows (Figure 6). LPS isolated from MG1655, which lacks an O-antigen, was unchanged in the presence of ciclopirox.…”
Section: Resultsmentioning
confidence: 94%
“…Based on examples from E. coli studies , the OMP profiles of E . coli rough mutants were substantially distinct from the profiles of smooth strains [ 29 , 30 , 31 ]. In this study, differences in the OMP profiles of mutants with truncated and smooth LPS were also observed, but it seems that truncated LPS did not significantly influence the composition of the OMPs ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Truncated LPS can affect bacterial stability and outer membrane permeability, leading to the remodeling of the structure of the outer membrane and altering the outer membrane composition of the cell wall [ 26 , 27 , 28 ]. For example, the OMP profiles of Escherichia coli rough mutants were substantially distinct from the profiles of smooth strains [ 29 , 30 , 31 ]. Live Salmonella with truncated LPS should expose more OMPs to the host immune system, but live Salmonella with deep rough LPS was unable to colonize and persist in the host organs and induced poor immunogenicity against OMPs [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is present in the outer leaflet of the outer membrane where it tightly interacts with porins and other outer membrane proteins (OMP) that determine the permeability of the envelope (Nikaido and Vaara, 1985;1987). A number of studies involving rough LPS mutants have demonstrated the importance of this component for the structural and functional integrity of the outer membrane and for bacterial virulence (Sukupolvi and Vaara, 1989;Marvin et al, 1989;Ried et al, 1990;Rivera et al, 1993;Vaara, 1993;Stanley et al, 1993;Laird et al, 1994;Fralick and Burns-Keliher, 1994;Sandlin et al, 1995;Schwan et al, 1995). Conversely, we show herein that the co-expression of two complete LPS cores (R1 plus endogeneous core) in recombinant V. cholerae may lead to impaired cell growth and division capability, as revealed by the high proportion of cell chains or filaments observed with strains carrying the r fa R1 genetic locus.…”
Section: Discussionmentioning
confidence: 99%